Pengaruh Performance Expectancy Dan Social Influence Terhadap Minat Beli Makanan Melalui Aplikasi Shopeefood - Marsha, Ifan; Rizal, Muhammad; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to see whether performance expectancy and social influence partially and simultaneously influence purchasing interest. The type of research used is explanatory research with a quantitative approach method. This research was conducted at the Islamic University of Malang using a research population of all active students, totaling 12,044 students. The sample obtained was 92 respondents using a non-probability sampling technique, namely snowball sampling. Performance expectancy and social influence simultaneously have a significant effect on purchasing interest. Performance expectancy has a significant effect on buying interest. Social influence has a significant effect on buying interest. Keywords: Performance Expectancy, Social Influence And Buying Interest.